Sosialisasi dan Pelatihan Sertifikasi Produk Halal Pada Pelaku Usaha Makanan di Padukuhan Sumberan Kecamatan Ngaglik Kabupaten Sleman - As’ari, Hasim; Suarsa, Abin; Purnama, Eka (Abdimas Indonesian Journal, 2024)
The government requires business actors to have a halal certificate by 2024. This PKM activity aims to socialize Law no. 33 of 2014 concerning Halal Product Guarantees, and business actors in Sumberan Hamlet, Ngaglik District, Sleman Regency, through socialization activities and halal certification training, are expected to be able to produce halal food products, thoyiban. This is because there is still a lack of business actors in Sumberan Hamlet who have halal certificates. The PKM method goes through an initial preparation stage, the implementation stage of PKM activities is carried out with lectures and a mentoring stage. PKM ran smoothly, participants were very enthusiastic about following stage by stage. Through this PKM, business actors in Sumberan Hamlet guarantee halal quality in their products in order to obtain halal certificates so that they can increase sales, and ultimately improve community welfare.